Pengaruh Kualitas Produk, Citra Merek, Dan Lifestyle Halal Terhadap Minat Beli Produk Skincare Somethinc (Studi Kasus pada Mahasiswa Kota Malang) - Ulya, Arifah Izzatul; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The objective of this research is to assess both the individual and collective impacts of product quality, brand image, and halal lifestyle on consumers' buying interest. The study focuses on a population of students residing in Malang City. A total of 90 respondents were selected as the sample, with the sample size determined using the hair formula due to the uncertainty surrounding the total population. This research employed a quantitative approach for data collection and analysis, utilizing SPSS software. The findings indicate that product quality, brand image, and halal lifestyle significantly influence purchase intention when considered together. Specifically, both product quality and brand image positively and significantly affect purchase intention, whereas halal lifestyle demonstrates a negative yet significant impact on purchase intention. Keywords: Product Quality, Brand Image, Halal Lifestyle, Purchase Intention